2011
DOI: 10.1089/acm.2010.0061
|View full text |Cite
|
Sign up to set email alerts
|

How Patients Choose Acupuncturists: A Mixed-Methods Project

Abstract: Objectives: Patients can have difficulties choosing acupuncturists in the United Kingdom because acupuncturists are not all subject to statutory regulation. Research has identified factors that influence patients' choice of general practitioner. However, how patients choose acupuncturists has not been studied. The aim was to investigate how patients choose acupuncturists and to identify which factors might influence this choice.Design: A mixed-methods design used an exploratory qualitative study followed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…Future study could ascertain the extent www.intechopen.com of 'secondary function' acupuncture locations and if these establishments are adequately meeting the demand for acupuncture services. Specifically, research could build on the findings of Bishop et al (2011), who determined that acupuncturists' trustworthiness and competence are important to potential customers, and establish if these and other patientcentered attitudes towards 'primary' and 'secondary' function acupuncture treatment vary over space. Giordano et al (2004) call for discourse regarding the mechanisms for which acupuncture therapies, and more widely Chinese traditional medicine and complementary and alternative health care approaches, could become more integrated into a jurisdiction's public health network.…”
Section: Discussionmentioning
confidence: 99%
“…Future study could ascertain the extent www.intechopen.com of 'secondary function' acupuncture locations and if these establishments are adequately meeting the demand for acupuncture services. Specifically, research could build on the findings of Bishop et al (2011), who determined that acupuncturists' trustworthiness and competence are important to potential customers, and establish if these and other patientcentered attitudes towards 'primary' and 'secondary' function acupuncture treatment vary over space. Giordano et al (2004) call for discourse regarding the mechanisms for which acupuncture therapies, and more widely Chinese traditional medicine and complementary and alternative health care approaches, could become more integrated into a jurisdiction's public health network.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results and discussion of Reid and Alfred (2013) is integrated, with neither method of data collection clearly favoured over another, lending credibility to the editorial argument. Bishop et al (2011) adopted a sequential exploratory, mixed methods design to investigate how patients choose their acupuncturist, using a qualitative method of semi-structured interviews followed by a quantitative factorial design. They stated a Pragmatic philosophical paradigm without giving any further details as to what pragmatism is or why it was chosen, yet this is a strength rarely observed in MMR in CAM.…”
Section: Use Of Mmr In Acupuncturementioning
confidence: 99%
“…Bishop et al (2011) discussed the potential factors that may relate to why people choose a particular health care practitioner, with same sex preferences emphasised in the literature (Bishop et al 2011). Their results indicated that some women would only attend a consultation with a male acupuncturist if they could bring along a chaperone, i.e.…”
Section: Recruitment and Attritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients deciding to try acupuncture are thus faced with choosing from many possible options 1 and value advice and recommendations from their social contacts, or lay referral networks. 1 2 However, use of acupuncture is not so widespread in the UK that everyone knows someone who has tried it-about 1.6% of the general population visited acupuncturists in 1998 3 and 2001, 4 while an estimated 3.9 million acupuncture treatments were delivered in 2009.…”
Section: Introductionmentioning
confidence: 99%